CRISPR/Cas9-Mediated Vitellogenin Receptor Knockout Leads to Functional Deficiency in the Reproductive Development of Plutella xylostella - Peng, Lu; Wang, Qing; Zou, Ming-Min; Qin, Yu-Dong; Vasseur, Liette; Chu, Li-Na; Zhai, Yi-Long; Dong, Shi-Jie; Liu, Li-Li; He, Wei-Yi; Yang, Guang; You, Min-Sheng (Frontiers in Physiology, 2020)
The vitellogenin receptor (VgR) belongs to the low-density lipoprotein receptor (LDLR) gene superfamily and plays an indispensable role in Vg transport, yolk deposition and oocyte development. For this reason, it has become a promising target for pest control. The involvement of VgR in Vg transport and reproductive functions remains unclear in diamondback moth, Plutella xylostella (L.), a destructive pest of cruciferous crops. Here, we cloned and identified the complete cDNA sequence of P. xylostella VgR, which encoded 1805 amino acid residues and contained four conserved domains of LDLR superfamily. PxVgR was mainly expressed in female adults, and specifically expressed in the ovary. Meanwhile, PxVgR protein also showed the similar expression profile with the PxVgR transcript. CRISPR/Cas9-mediated PxVgR knockout created a homozygous mutant of P. xylostella with 5-bp-nucleotide deletion in the PxVgR. The expression deficiency of PxVgR protein was detected in the ovaries and eggs of mutant individuals. Vg protein was still detected in the eggs of the mutant individuals, but with a decreased expression level. However, PxVg transcripts were not significantly affected by the PxVgR knockout. Knockout of PxVgR resulted in shorter ovarioles of newly emerged females. No significant difference was detected in the number of eggs laid within three days between wild and mutant individuals, but the loss of PxVgR gene caused smaller and whiter egg and lower egg hatching rate. This is a first report on the functions of VgR in Vg transport, ovary development, oviposition and embryonic development of P. xylostella using CRISPR/Cas9 technology. This study lays the foundation for understanding molecular mechanisms of P. xylostella reproduction, and for making use of VgR as a potential genetic-based molecular target for better control of the P. xylostella.